Informatics and Communication Technologies for Societal Development: Proceedings of ICICTS 2014 - Rajsingh, Elijah Blessing (Springer, 2015)
This volume comprises research papers presented at the International Conference on Informatics and Communication Technologies for Societal Development (ICICTS 2014) held at Karunya University, India. The content focuses on the recent advancements in image or signal processing, computer vision, communication technologies, soft computing, advanced computing, data mining and knowledge discovery. The primary objective of this volume is to facilitate advancement and application of the knowledge and to promote ideas that solve problems faced by society through cutting-edge technologies. The chapters contain selected articles from academicians, researchers and industry experts in the form of frameworks, models and architectures. Practical approaches, observations and results of research that promotes societal development are also incorporated. This volume will serve as a useful compendium for interested readers and researchers working towards societal development from the technological perspective.